MicroRNA-10 modulates Hox genes expression during Nile tilapia embryonic development. (May 2016) - Giusti, Juliana; Pinhal, Danillo; Moxon, Simon; Campos, Camila Lovaglio; Münsterberg, Andrea; Martins, Cesar
Abstract: Hox gene clusters encode a family of transcription factors that govern anterior–posterior axis patterning during embryogenesis in all bilaterian animals. The time and place of Hox gene expression are largely determined by the relative position of each gene within its cluster. Furthermore, Hox genes were shown to have their expression fine-tuned by regulatory microRNAs (miRNAs). However, the mechanisms of miRNA-mediated regulation of these transcription factors during fish early development remain largely unknown. Here we have profiled three highly expressed miR-10 family members of Nile tilapia at early embryonic development, determined their genomic organization as well as performed functional experiments for validation of target genes. Quantitative analysis during developmental stages showed miR-10 family expression negatively correlates with the expression of HoxA3a, HoxB3a and HoxD10a genes, as expected for bona fide miRNA–mRNA interactions. Moreover, luciferase assays demonstrated that HoxB3a and HoxD10a are targeted by miR-10b-5p. Overall, our data indicate that the miR-10 family directly regulates members of the Hox gene family during Nile tilapia embryogenesis. Highlights: Two Hox genes were appointed as targets by miR-10 family. Negative correlations were observed in the expression of and miR-10b-5p and HoxB3a and HoxD10a genes. Micro-RNAs and target genes are closed located in the genome.